2011
DOI: 10.1002/dc.21742
|View full text |Cite
|
Sign up to set email alerts
|

Prolapsed fallopian tube: Cytological findings in a ThinPrep liquid based cytology vaginal vault sample

Abstract: Fallopian tube prolapse through the vaginal vault after hysterectomy is a rare complication. The clinical diagnosis is difficult and the patient may undergo unnecessary treatment. A cytological diagnosis of tubal prolapse is rare. There are very few descriptions of the cytological appearances of prolapsed fallopian tube and to our knowledge, they have not been described in liquid based cytology preparations. The presence of classic columnar cells with cilia and sheets of cells with small granular uniform nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…8,11 Few authors have highlighted the presence of large, crowded hyperchromatic nuclei, while some have highlighted the presence of three-dimensional groups of columnar cells as well as squamous metaplastic cells with mild nuclear atypia and leucophagocytosis. 7,10 The presence of colum- Though the prolapse occurs on its own, spontaneous resolution is…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,11 Few authors have highlighted the presence of large, crowded hyperchromatic nuclei, while some have highlighted the presence of three-dimensional groups of columnar cells as well as squamous metaplastic cells with mild nuclear atypia and leucophagocytosis. 7,10 The presence of colum- Though the prolapse occurs on its own, spontaneous resolution is…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the literature revealed five previous reports highlighting the cytomorphologic features of FTP in vault smears. [7][8][9][10][11] The clinical, cytological as well as histopathologic details of all the reported cases have been presented in Table 1.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Imaging diagnostic studies may pose a diagnostic pitfall, even with the use of advanced modalities such as pelvic MRI and biopsy of the prolapsed tissue. Vaginal cuff cytology can demonstrate squamous or glandular cells, often with superimposed granulation changes or reactive atypia secondary to chronic inflammation [17][18][19]. Histopathology remains the only means of definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%